Pedigree analysis of the racing line Quarter Horse: genetic diversity and most influential ancestors - Faria, R.A.S. (2021)
The aims of this study were to evaluate the genetic diversity of the racing line Quarter Horse breed in Brazil and to provide data on the most influential ancestors by pedigree analysis. All horses that had participated in sprint races in Brazil between 1978 and 2016 were evaluated. There were 5,861 athletes horses (2,474 males and 3,387 females) born between 1971 and 2014. These animals were referred to as the racing population (Pr), which was divided into three subpopulations to evaluate three complete decades (84.5% of Pr). These subpopulations consisted of 1,712, 1,604 and 1,461 animals born in the 1980s (sP80), 1990s (sP90) and 2000s (sP00), respectively. The quality of the pedigree was assessed based on the number of complete equivalent generation traced. There were 5.4 (Pr), 4.7 (sP80), 5.7 (sP90) and 6.3 (sP00) generations, which permitted accuracy of the conclusions reported. The generation intervals were long, with 13.2 (sire-son/daughter) and 10.6 (dams-son/daughter) years (Pr). The coefficients of inbreeding and average relatedness were 0.95% and 1.84% for Pr and 1.60% and 2.56% for sP00, respectively. In Pr and sP00, the effective population size (Ne) based on ΔFi was 215 and 144, respectively, with 68 and 41 animals per generation. The probability of gene origin given by the effective number of founders (fe), ancestors (fa) and founder genome equivalents (fge) was 192, 61 and 34, respectively, for Pr, with considerable losses of genetic diversity over the last decades evaluated. The number of ancestors (founders or not) that explained the total genetic diversity was 1,587. This number is considered high; however, only 32 and 9 ancestors explained 50% of the genetic diversity of Pr and sP00, respectively. The 10 most influential ancestors of sP00 explained 52.2% of the total genetic diversity. The loss of genetic diversity and concentration in a reduced number of breeding animals indicate failures in the breeding and conservation programs of the racing line. Mating designs in conjunction with the selection of breeding animals should be promoted and goals should be defined for racing line of the Quarter Horse breed in Brazil.